Idealizm a natura stosunku intencjonalnego - Czerniawski, Jan (Filozofia Nauki, 1998)
If metaphysical realism could be equated with epistemological realism and the latter with representationism, then impossibility of representationism would imply impossibility of both realisms. However, at least the second identification is illegitimate, since a presentationist realism is possible. Its alleged impossibility results from misconceiving the intentional relation as consisting in creating the intentional correlate of mental act. In fact, such act, at least in the case of non-divine subject, never creates its intentional object, but only ascribes various properties - and sometimes real existence or non-existence - to it. Even in the case of literary fiction there is no genuine creation of invented characters, since the author is unable of making them existing. If the intentional object exists, then some of its actual properties may differ from the ones ascribed to it. The above solution makes possible to relate our cognitive acts directly to the reality «in itself» and not to its phenomenal «representation» in Kantian style.